Implementation of ANN-CFB Methods in Measuring Community Satisfaction Level of Denpasar City on the Aspect of Government Services - Santiyasa, I Wayan; Kusumayanti, Luh Eka (Advances in Tropical Biodiversity and Environmental Sciences, 2019)
The concept of a smart city is indeed presented as an answer for efficient management of resources. Support for applications that are constantly evolving and the creation of a creative ecosystem in the field of technology, is a good first step towards a smart city. But in reality smart city is not only related to technology. This concept is a combination of new technology and intelligent thinking about the use of technology. As a city full of allure, Denpasar City along with its development and population growth, began to emerge various problems such as decreasing the quality of public services, congestion on the road, accumulation of garbage and other social problems. To solve these problems, Denpasar needs a smart, creative and innovative solution run by the ranks of government officials, from leaders to the lowest levels, and supported by the full commitment of all its citizens. Various efforts have been made by the Denpasar City government to facilitate services to the community, ranging from building a system to facilitate services to the community such as the health service system, population service system, government service system (e-Gove), and the public complaints system. To find out whether the efforts made by the government are related to the services provided to the community by implementing a smart city system. In this study various measurements of satisfaction levels were carried out to obtain significant conclusions. Of the five aspects studied, namely aspects of government services, aspects of government transparency, aspects of health services, aspects of population service, aspects of transportation services and aspects of water supply and electricity services, in general the people of Denpasar expressed satisfaction with a level of satisfaction of 76,312 and the level of satisfaction with aspects of health services have the highest level of satisfaction that is equal to 88,574.